Long-term endothelial dysfunction in irradiated vessels: an immunohistochemical analysis Langzeit-Endothelfunktionsstörung in bestrahlten Gefäßen: immunhistochemische Analyse - Preidl, Raimund; Möbius, Patrick; Weber, Manuel; Amann, Kerstin Ute; Neukam, Friedrich Wilhelm; Kesting, Marco Rainer; Geppert, Carol-Immanuel; Wehrhan, Falk (Strahlentherapie und Onkologie, 2019)
Background: Microvascular free flap reconstruction has become a standard technique in head and neck reconstructive surgery. Pre-operative radiotherapy is associated with a higher incidence of free flap malperfusion and the need for operative revision. Irradiated vessels present characteristic histomorphological and structural changes. Alterations in endothelial cells of irradiated arteries remain incompletely investigated especially with regard to long-term changes in endothelial dysfunction supporting an intraluminal pro-thrombotic and pro-inflammatory milieu. Methods: Endothelial expression of intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), E‑ and P‑selectin, endothelial NO-synthase (eNOS), thrombomodulin and plasminogen activator inhibitor-1 (PAI-1) in irradiated and non-irradiated arteries was analysed using immunohistochemistry and Remmele scale grading. The average radiation dose was 58.7 ± 7.0 Gy; the time interval between end of radiation and tissue sampling was 106.0 ± 86.8 months. Results: Endothelial expression of ICAM-1, VCAM-1, E‑ and P‑selectin as well as PAI-1 was significantly increased in previously irradiated arteries compared with non-irradiated controls, whereas thrombomodulin and eNOS expression did not show any differences. However, when comparing non-irradiated free flap arteries with irradiated arteries from the head and neck area in respective individuals, eNOS expression was significantly lower in irradiated vessels whereas ICAM-1, VCAM-1, E‑/p-Selectin and PAI-1 showed significantly higher expression levels. Conclusion: There is ongoing endothelial dysfunction in terms of increased expression of pro-thrombotic and pro-inflammatory markers in irradiated arteries even years after radiotherapy. Treating this endothelial dysfunction might reduce the complication rates associated with microvascular free flap reconstructions in irradiated patients.
CRIS-Team Scopus Importer:2019-05-03
Keywords: Endothelial dysfunction; Free tissue flaps; Radiation dosage; Radiotherapy; Reconstructive surgery